Etika Pedagang Sembako Pesepektif Bisnis Islam Di Indonesia - heri Irawan (Jurnal Ilmiah Ekonomi Islam, 2023)
Swordsmen and Muslim-majority business people. But based on the facts, there are still many people who violate ethics in trading. The formulation of the problem is how to understand and how apply Islamic business ethics to staple food traders in the Sinjai central market. This study aims to explain the understanding and application of Islamic business ethics exemplified by the Prophet Muhammad saw., to staple food traders in the Sinjai Central Market. This type of research is field research with qualitative methods that are carried out in the descriptive analysis. The study was carried out in the Sinjai patent, the capital of South Sulawesi Province. The results showed that: the majority of staple food traders in the Sinjai Central Market have understood and applied Islamic business ethics as exemplified by the Prophet Muhammad saw in trading. This can be seen from the indicators of staple food traders about understanding business ethics reaching 19 people or 95% and staple food traders carrying out an attitude of honesty reaching up to 19 people from 20 informants or 95%. Keywords : Ethics, Islamic Business